Practical mobile ad hoc networks for large scale cattle monitoring - Wietrzyk, Bartosz (2008)
This thesis is concerned with identification of realistic requirements for the cattle monitoring system and design of the practical architecture addressing these requirements. Automated monitoring of cattle with wireless monitoring devices mounted on the animals can increase efficiency of cattle production, decrease its reliance on human labour and thus increase its profitability. Multi-hop ad hoc wireless communication has the potential to increase battery life of the animal mounted devices, decrease their size and combat disconnections. This thesis reveals that no current approach sufficiently addresses energy constrains of the animal mounted devices and potential disconnections.